Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $H : \mathbb{R} \to \mathbb{R}$ denote the Heaviside function:

$$ H(y) = \begin{cases} 0 & y < 0, \\ 1 & y \ge 0. \end{cases} $$

Suppose that $c > 1$ is fixed with $t$ ranging over $\mathbb{R}$. Prove that: $$ \int_0^\infty H(t + (1- \frac{1}{c})y - 1)H(t - \frac{y}{c})dy = \begin{cases} 0 & t < \frac{c}{2c-1}, \\ \frac{c}{c-1}((2c-1)t-c) & \frac{c}{2c-1} \le t \le 1, \\ ct & t > 1. \end{cases} $$

This integral appears in a research paper (on inverse problems) that I've been studying. I've been trying to work out all the cases for awhile.

The case $t >1$ is easy enough to work out. In that situation, $t + (1 - \frac{1}{c})y - 1 > (1 - \frac{1}{c})y \ge 0$, all $y \ge 0$. And $t - \frac{y}{c} \ge 0 \iff y \le ct$ Hence, $H(t + (1- \frac{1}{c})y - 1)H(t - \frac{y}{c})$ = 1 for $y \in [0,ct]$ and $0$ otherwise (this gives the correct answer for $t > 1$).

With the other cases, my main stumbling point is determining why the function should behave differently as we cross $t = \frac{c}{2c-1}$.

Hints or solutions are greatly appreciated.

share|improve this question
1  
Is there any more information? What I got is $0\ (t\lt 1/c)$, $c(t-1)/(c-1)$$\ (1/c\le t\le 1)$, $ct\ (t\gt 1).$ So far, I can't find any mistakes in my try. –  mathlove Dec 28 '13 at 5:14
    
I agree with your answer (@MoonKnight got the same one too). For completeness sake, here is a link to the paper: iopscience.iop.org/0266-5611/29/6/065001 This problem appears on page 6. –  jtms88 Dec 28 '13 at 22:27

2 Answers 2

up vote 1 down vote accepted

I don't know how you get the result but it seems wrong to me.

$H(..)H(..)\neq 0$ requires

  1. $t-y/c\ge 0 \Rightarrow y \le ct$
  2. $t+(1-1/c)y-1\ge 0 \Rightarrow y\ge c(1-t)/(c-1)$

If $1\ge t\ge 1/c$, then $0\le c(1-t)/(c-1)\le ct$. then the integral gives $$ \int_0^\infty H(...)H(...)dy = ct-c\frac{1-t}{c-1}=\frac{c}{c-1}(ct-1) $$

If $t\le 1/c$, then $c(1-t)/(c-1)\ge ct$, thus $\forall y\ge0 ,H(..)H(...)=0$. So the integral gives 0.

share|improve this answer
    
Thank you! Yes the published answer seems to be wrong, I guess. This solution you have written is very clear. –  jtms88 Dec 28 '13 at 22:24

$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,}% \newcommand{\dd}{{\rm d}}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\half}{{1 \over 2}}% \newcommand{\ic}{{\rm i}}% \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\ol}[1]{\overline{#1}}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ We'll use the identity $\ds{% {\rm H}\pars{x} \equiv \int_{-\infty}^{\infty}{\dd k \over 2\pi\ic}\, {\expo{\ic kx} \over k - \ic 0^{+}}}$

\begin{align} ? &\equiv \int_{0}^{\infty}{\rm H}\pars{t + \bracks{1- {1 \over c}}y - 1} {\rm H}\pars{t - {y \over c}}\,\dd y = \int_{0}^{\infty}{\rm H}\pars{{c\bracks{1 - t} \over c - 1} - y}{\rm H}\pars{ct - y}\,\dd y \\[3mm]&= \int_{0}^{\infty}{\rm H}\pars{\min\braces{ct,{c\bracks{1 - t} \over c -1}} - y}\,\dd y \end{align}
  1. $\ds{ct < {c\pars{1 - t} \over c - 1}\quad\imp\quad c^{2}t - ct < c - ct\quad\imp\quad t < {1 \over c}}$ $$ ? = \int_{0}^{\infty}{\rm H}\pars{ct - y}\,\dd y = {\rm H}\pars{t}\int_{0}^{ct}\dd y = {\rm H}\pars{t}ct $$
  2. $\ds{t > {1 \over c}}$ $$ ? = \int_{0}^{\infty}{\rm H}\pars{{c\bracks{1 - t} \over c - 1} - y}\,\dd y = {\rm H}\pars{1 - t}\int_{0}^{c\pars{1 - t}/\pars{c - 1}}\,\dd y = {\rm H}\pars{1 - t}\,{c\pars{1 - t} \over c - 1} $$
$$ ?=\left\lbrace% \begin{array}{lcl} 0 & \mbox{if} & t < 0\ \wedge\ t > 1 \\ ct & \mbox{if} & 0 \leq t < {1 \over c} \\ {c \over c - 1}\,\pars{1 - t} & \mbox{if} & {1 \over c} \leq t < 1 \end{array}\right. $$
share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.